Attenuation hotspots in neurotropic human astroviruses. - Hashim Ali; Aleksei Lulla; Alex S Nicholson; Jacqueline Hankinson; Elizabeth B Wignall-Fleming; Rhian L O'Connor; Diem-Lan Vu; Stephen C Graham; Janet E Deane; Susana Guix; Valeria Lulla (PLoS Biology)
During the last decade, the detection of neurotropic astroviruses has increased dramatically. The MLB genogroup of astroviruses represents a genetically distinct group of zoonotic astroviruses associated with gastroenteritis and severe neurological complications in young children, the immunocompromised, and the elderly. Using different virus evolution approaches, we identified dispensable regions in the 3' end of the capsid-coding region responsible for attenuation of MLB astroviruses in susceptible cell lines. To create recombinant viruses with identified deletions, MLB reverse genetics (RG) and replicon systems were developed. Recombinant truncated MLB viruses resulted in imbalanced RNA synthesis and strong attenuation in iPSC-derived neuronal cultures confirming the location of neurotropism determinants. This approach can be used for the development of vaccine candidates using attenuated astroviruses that infect humans, livestock animals, and poultry.